Assessment of the relationship of costs, sales and profits in the refinery production on the example of LLP «Atyrau Refinery» (Journal of Economic Research & Business Administration, 2016)
Each organization in order to maximize profits, not only seeks to in- crease production, improve competitiveness and other factors to improve the accounting of expenses for production and sales of products, but also need to organize the reduction of production costs. Problems of cost re- duction is a hot topic of discussion in today’s economic environment. After all, the solution of this problem allows organizations to become competi- tive, to have a good economic potential. The main feature in the refinery is the continuity and duration of the production process and the relative stability of the size of the work in progress.